The competitive potential of the advanced technology sector - Łada, Magdalena (Potencjał konkurencyjny sektora zaawansowanej technologii, 2019)
The increasing use of advanced technologies by enterprises increases the importance of the advanced technology sector in national economies. For this reason, the purpose of the research presented in the study was to determine the competitive potential of the advanced technology sector on the intra-EU market in recent years. The evaluation was conducted using the labour productivity index, labour costs and the share of the number of high technology sector enterprises in the total number of enterprises in the EU sector. Based on partial indicators, a synthetic indicator was built which allowed for the precise determination of the potential of each of the countries studied. Enterprises in countries with a strong and stable economy have higher potential, are more developed and more easily tackle the new challenges that occur in the economy. Enterprises with low competitive potential are located primarily in smaller countries with smaller support possibilities. The decisive factor was, above all, the high productivity of work
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 7, s. 60-73
Keywords: competitive potential; high technology sector; labour productivity; labour costs; European Union; potencjał konkurencyjności; sektor zaawansowanej technologii; produktywność pracy; koszty pracy; Unia Europejska